The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1743-7075-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Onion peel extracts ameliorate hyperglycemia and insulin resistance in high fat diet/streptozotocin-induced diabetic rats

Abstract: BackgroundQuercetin derivatives in onions have been regarded as the most important flavonoids to improve diabetic status in cells and animal models. The present study was aimed to examine the hypoglycemic and insulin-sensitizing capacity of onion peel extract (OPE) containing high quercetin in high fat diet/streptozotocin-induced diabetic rats and to elucidate the mechanism of its insulin-sensitizing effect.MethodsMale Sprague-Dawley rats were fed the AIN-93G diet modified to contain 41.2% fat and intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 37 publications
10
103
2
3
Order By: Relevance
“…The authors of those studies which found positive effects of quercetin on glycemic control proposed several mechanisms to explain the beneficial effect of this polyphenol: (a) the anti-oxidative protective action on the pancreatic islets (Coskun et al 2005;Babujanarthanam et al 2010;Jeong et al 2012), (b) the increase in adiponectin circulating concentration (Wein et al 2010), (c) the inhibition of small intestine glucosidase activity , (d) the reduction in the intestinal glucose absorption mediated by GLUT2 (Kwon et al 2007), (e) the increase in glucokinase activity (Vessal et al 2003) and (f) the increase in GLUT4 transporters in skeletal muscle (Jung et al 2011;Shen et al 2012;AnhĂȘ et al 2012).…”
Section: Controlmentioning
confidence: 99%
“…The authors of those studies which found positive effects of quercetin on glycemic control proposed several mechanisms to explain the beneficial effect of this polyphenol: (a) the anti-oxidative protective action on the pancreatic islets (Coskun et al 2005;Babujanarthanam et al 2010;Jeong et al 2012), (b) the increase in adiponectin circulating concentration (Wein et al 2010), (c) the inhibition of small intestine glucosidase activity , (d) the reduction in the intestinal glucose absorption mediated by GLUT2 (Kwon et al 2007), (e) the increase in glucokinase activity (Vessal et al 2003) and (f) the increase in GLUT4 transporters in skeletal muscle (Jung et al 2011;Shen et al 2012;AnhĂȘ et al 2012).…”
Section: Controlmentioning
confidence: 99%
“…Recent literature is rich in both in vivo and in vitro studies reporting the antithrombotic (Lee et al, 2013), hypolipidemic (Lee et al, 2012b;Srinivasan, 2013), antidiabetic (Jung et al, 2011), antiobesity (Yoshinari et al, 2012), antioxidant (Alpsoy et al, 2013;Lee et al, 2012a), anti-inflammatory (Dorsch et al, 1990), cancer chemopreventive (Wang et al, 2012), and antiparasitic (Aboelhadid et al, 2013;Klimpel et al, 2011) properties of onion bulb extracts. Moreover, accumulated epidemiological studies suggest that a diet rich in onions may also have favorable effects on the risk of acute myocardial infarction (Galeone et al, 2009), and benign prostatic hyperplasia (Galeone et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that quercetin has antidiabetic effect like metformin [27]. Quercetin, present in onion peel extracts, improved insulin sensitivity by up-regulating expressions of insulin receptor and glucose transporter as well as by promoting metabolism of glucose in peripheral tissues in diabetic rats [28]. This study can partly help to this claim that PFF due to have quercetin could lower glucose concentration.…”
Section: Discussionmentioning
confidence: 51%